Evolution of the Plasmodium vivax multidrug resistance 1 gene in the Greater Mekong Subregion during malaria elimination - Huguette Gaelle Ngassa Mbenda (2020)
© 2020 The Author(s). Background: The malaria elimination plan of the Greater Mekong Subregion (GMS) is jeopardized by the increasing number of Plasmodium vivax infections and emergence of parasite strains with reduced susceptibility to the frontline drug treatment chloroquine/primaquine. This study aimed to determine the evolution of the P. vivax multidrug resistance 1 (Pvmdr1) gene in P. vivax parasites isolated from the China-Myanmar border area during the major phase of elimination. Methods: Clinical isolates were collected from 275 P. vivax patients in 2008, 2012-2013 and 2015 in the China-Myanmar border area and from 55 patients in central China. Comparison was made with parasites from three border regions of Thailand. Results: Overall, genetic diversity of the Pvmdr1 was relatively high in all border regions, and over the seven years in the China-Myanmar border, though slight temporal fluctuation was observed. Single nucleotide polymorphisms previously implicated in reduced chloroquine sensitivity were detected. In particular, M908L approached fixation in the China-Myanmar border area. The Y976F mutation sharply decreased from 18.5% in 2008 to 1.5% in 2012-2013 and disappeared in 2015, whereas F1076L steadily increased from 33.3% in 2008 to 77.8% in 2015. While neutrality tests suggested the action of purifying selection on the pvmdr1 gene, several likelihood-based algorithms detected positive as well as purifying selections operating on specific amino acids including M908L, T958M and F1076L. Fixation and selection of the nonsynonymous mutations are differently distributed across the three border regions and central China. Comparison with the global P. vivax populations clearly indicated clustering of haplotypes according to geographic locations. It is noteworthy that the temperate-zone parasites from central China were completely separated from the parasites from other parts of the GMS. Conclusions: This study showed that P. vivax populations in the China-Myanmar border has experienced major changes in the Pvmdr1 residues proposed to be associated with chloroquine resistance, suggesting that drug selection may play an important role in the evolution of this gene in the parasite populations.[Figure not available: see fulltext.]